Who posts performance bonds and why? Evidence from China's CEOs - Bryson, Alex; Forth, John; Zhou, Minghai (Elsevier, 2014)
Despite their theoretical value in tackling principal–agent problems at low cost to firms there is almost no empirical literature on the prevalence and correlates of performance bonds posted by corporate executives. We show that they are an important feature in today's CEO labour market in China: around one-tenth of corporations deploy performance bonds and they are equivalent to around 14% of CEO cash compensation. Consistent with principal–agent theory bonds are negatively associated with firm sales volatility. The complementarity between bonds and other incentive mechanisms such as bonuses and stock holding is consistent with optimal reward structures for multi-tasking agents. Those CEOs posting bonds are higher in the Communist Party ranks, were promoted via tournaments, and run larger firms, findings consistent with using bonds as an incentive to attract and retain the most able workers. Although state-owned enterprises are just as likely as privately owned ones to use bonds in CEO contracts, some of the theoretical predictions which assume profit-maximising firms do not hold where the state has an ownership stake.